The sexual education of Edith Wharton - Erlich, Gloria C. (University of California Press, 1992)
Starting with the tensions in the early family constellation, Gloria C. Erlich traces Edith Wharton's erotic evolution--from her early repression of sexuality and her celibate marriage to her discovery of passion in a rapturous midlife love affair with the bisexual Morton Fullerton. Analyzing the novelist's life, letters, and fiction, Erlich reveals several interrelated identity systems--the filial, the sexual, and the creative--that evolved together over the.
Keywords: Wharton, Edith, -- 1862-1937 -- Psychology.; Wharton, Edith, -- 1862-1937 -- Knowledge -- Psychology.; Wharton, Edith, -- 1862-1937 -- Relations with men.; Wharton, Edith, -- 1862-1937; Women and literature -- United States -- History -- 20th century.; Psychological fiction, American -- History and criticism.; Authors, American -- 20th century -- Psychology.; Femininity in literature.; Psychoanalysis and literature.; Women in literature.; Sex in literature.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Écrivains américains -- 20e siècle -- Psychologie.; Féminité dans la littérature.; Psychanalyse et littérature.; Femmes dans la littérature.; Sexualité dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM / American / General; Authors, American -- Psychology; Femininity in literature; Relations with men; Psychoanalysis and literature; Psychological fiction, American; Psychology; Sex in literature; Women and literature; Women in literature; United States; Seksualiteit.; 1900-1999; English fiction; Criticism, interpretation, etc.; History